Adhesion prevention in laparoscopic myomectomy - Pao-Ling Torng (Wolters Kluwer Medknow Publications, 2014)
Adhesions are common sequels of laparoscopic myomectomy (LM), even though they are much reduced compared with laparotomy. Good surgical technique is the main principle to reduce post LM adhesion. Based on electronic research of the PubMed database using specific keywords, barrier materials offer promise for adhesion prevention at second look laparoscopy. However, pregnancy outcome when influenced by adhesion formation after LM is unclear and warrants further investigation.